IMPACT OF PATHOGENS ON BIOFILM FORMATION OF PROBIOTIC CANDIDATE LACTOBACILLUS ACIDOPHILUS ATCC 314 AS A TREATMENT FOR STUNTING CASES - Taqwati Fadia Triasandita, Fira
Stunting is a chronic long-term malnutrition condition experienced by children during the first 1000 days of life due to poor nutrition and repeated infections. Children are categorized as stunted if their height-for-age is < -2 SD below the median child growth standards according to WHO. The presence of more pathogenic bacteria compared to commensal bacteria, including probiotics, can lead to an imbalance of gut microbiota, also known as gut dysbiosis. The presence of probiotics and their ability to form biofilms in the digestive tract can inhibit the formation of biofilms by pathogenic bacteria, primarily through a competition mechanism to prevent pathogen colonization.The objectives of this research are: (1) To determine the growth curve of L. acidophilus ATCC 314 bacteria, (2) To determine the minimum concentration for biofilm formation of L. acidophilus ATCC 314 through biofilm assay in skim milk and Luria Bertani (LB) media, and (3) To determine the interaction and abundance of L. acidophilus ATCC 314 challenged by Staphylococcus sp. M and Staphylococcus sp. N through biofilm assay in skim milk media. In this study, L. acidophilus ATCC 314 was used as a probiotic candidate, and pathogens used were Staphylococcus sp. M and Staphylococcus sp. N. The growth curve of L. acidophilus ATCC 314 was created in Lactobacillus MRS media, with an incubation temperature of 37°C for 24 hours without agitation, a working culture volume of 180 mL, and a 10% (v/v) inoculum with an initial density of 107 CFU/mL. Growth curve data in CFU/mL were taken every 3 hours over 24 hours in duplicate. Subsequently, a biofilm assay was conducted to determine the minimum concentration for biofilm formation of L. acidophilus ATCC 314 using Luria Bertani (LB) and skim milk media, including concentration variations of 102, 103, 104, and 106 CFU/mL. Biofilm formation was measured at four times using crystal violet as a biofilm layer stain. Biofilm-forming ability at various concentrations was measured at 595 nm absorbance in triplicate. Similarly, a biofilm interaction assay was conducted between L. acidophilus ATCC 314 (106 CFU/mL) and pathogens Staphylococcus sp. M 10% and Staphylococcus sp. N 10% in 200 ?L skim milk media with concentration variations of 103, 104, 105, 106, and 107 CFU/mL. An interaction test was then conducted to observe the composition between the probiotic and pathogen formed through the enumeration of planktonic and biofilm cells using a pathogen inoculum of 103 CFU/mL for both Staphylococcus sp. M and Staphylococcus sp. N isolates and 106 CFU/mL for L. acidophilus ATCC 314. The abundance of L. acidophilus ATCC 314 was quantified using MRS Agar, while Staphylococcus sp. M and Staphylococcus sp. N were quantified using Staphylococcus Agar. The study results showed a logarithmic phase from 0 to 12 hours and a generation time of 0.3 hours through the growth curve. Through biofilm assay, the minimum concentration for biofilm formation was obtained at 106 CFU/mL in skim milk and Luria Bertani (LB) media. Based on interaction tests, an increase in biofilm absorbance of L. acidophilus ATCC 314 was observed at 18 hours with a strong biofilm-former (SBF) category at each pathogen concentration (Staphylococcus sp. M and Staphylococcus sp. N), and biofilm formation inhibition concentrations of 103 and 107 CFU/mL for both pathogens were obtained. The final abundance of L. acidophilus ATCC 314 was obtained at 108 CFU/mL in interaction tests, and it was observed that the biofilm formed by L. acidophilus ATCC 314 could maintain its dominance when infected by Staphylococcus sp. M and Staphylococcus sp. N, with Staphylococcus sp. N showing higher pathogenicity compared to Staphylococcus sp. M. This was indicated by an increase in planktonic cell concentration of L. acidophilus ATCC 314 by about 1 log at 7 to 12 hours, along with a decrease of about 0.5 log at 12 hours in biofilmforming cell concentration of L. acidophilus ATCC 314. The biofilm formation by L. acidophilus can prevent pathogenic bacterial colonization in the gut, making L. acidophilus ATCC 314 a good probiotic candidate for preventing stunting cases in Indonesia.